Improving Speaking Confidence and Delivery Performance through Toastmasters-Based Evaluation Sessions: A Case Study of English Literature Students - Siska Mustikawati Hasibuan; Salsabila Eka Ananda; Rita Hartati (PT. Intelek Cendikiawan Nusantara, 2026)
This research originates from the problem of low confidence and public speaking performance among English Literature students, which is often triggered by a rigid numerical assessment system. This qualitative case study was conducted at Universitas Negeri Medan to evaluate the effectiveness of implementing Toastmasters-based evaluation sessions as an alternative assessment model. Through direct observation and structured questionnaires, the findings show that systematic feedback loops are able to improve both the psychological and technical aspects of students simultaneously. The data indicate that 70% of respondents felt calmer and more confident due to the supportive evaluation environment. Technically, there was a significant improvement in eye contact and a reduction of filler words by 86.7%, where all participants (100%) agreed that systematic feedback was far more effective than traditional numerical grading. The uniqueness of this research lies in the transition toward a “micro-evaluative” model that empowers students to take on specific roles such as Ah-Counter and Timer to develop deeper technical awareness. The study concludes that the integration of structured peer feedback is a key factor in bridging the gap between theoretical linguistic knowledge and professional communication competence.